El dibujo como experiencia sensible - García, Andrea C. (2018)
The architect 'occupies' the space he is projecting, he goes through it, he lives it; inscribing / carving in him all his empirical, sensory baggage. There is an emotional, personal connection with work in the process of gestation. Drawing as a sensitive experience is part and protagonist of the design thinking process. In the context of the workshop, it will be important to emphasize 'the sensitive' as a robust basis to receive and process in an original, personal and unique way, everything that the current global world invites.